'The dogma is the drama': participation and sacramentality in the plays of Dorothy L. Sayers - Wiedemann Hunt, Margaret (2017)
Dorothy L. Sayers’s first festival play, The Zeal of Thy House (1937), was written at a time when it was widely believed among Christian drama practitioners that drama itself has a sacramental significance. This conviction took on a new urgency for Sayers as theologians and church people sought ways of establishing Christianity as a basis on which to rebuild society after the Second World War. Sayers’s The Mind of the Maker (1941), a study in theological aesthetics intended as a contribution to public debate about post-war reconstruction, outlined a trinitarian and sacramental model for human work considered as a creative activity. Sayers wrote three more festival plays between 1939 and 1951, and this study examines the four plays in the light of her sacramental emphasis. It locates Sayers’s dramatic practice in the context of those Roman and Anglo-Catholic practitioners of the arts who embraced the neo-Thomism of the French philosopher Jacques Maritain, and examines the influence of William Temple and his belief in the sacramentality of the whole material creation. The study argues that while the festival plays have the background of timeless sacramentality noted by a number of commentators, Sayers takes sacramentalism further in all four plays with the onstage enactment of a timebound sacramental event in which the protagonist, estranged from God by an imbalance in the dynamic trinitarian flow within his creative self, experiences anagnorisis, repentance and the hope of restoration to the community of believers. This sacramental enactment becomes a model for the audience’s participative reception of the play itself, and the study uses insights from contemporary theorists of medieval drama to elucidate the nature of the dramatic experience in which theatre and sacrament become reciprocally paradigmatic. The belief that art and theology can critique each other was central to Sayers’s approach to dramatising the gospels in her wartime BBC radio life of Christ, The Man Born to be King, and a chapter on this play examines its participatory hermeneutics as an extension of the sacramentality of the stage plays. A final section locates Sayers’s concept of the ‘passionate intellect’ in relation to the mid-century theological tension between faith and reason. Few commentators have given Sayers’s four plays equal weight, and many have omitted her last play. This study aims to unite literary and theological methodologies in arguing that Sayers’s festival plays demonstrate an increasingly participative sacramentality that culminates in the onstage baptism of the final play, written for the Festival of Britain, The Emperor Constantine.